Avaliação dos efeitos da Terapia de Fotobiomodulação (TFBM) no alívio da dor em indivíduos com lombalgia - Vieira, Alexandre Arante Ubilla (2020)
Low back pain is one of the main causes of reduced quality of life and disability, also considered the leading cause of disability worldwide, this condition causes a large number of the absence in jobs and excessive costs for health systems. Physical therapy offers different types of treatment for low back pain, aiming to provide pain relief and restore structural and functional properties. The use of photobiomodulation therapy has shown satisfactory results in the attenuation of chronic pain in the lumbar region, but more work has to be performed in order to establish a standard of use. Therefore, the objective of this study is to evaluate the effects of PBMT with the LEAP SportsPod® device in the relief of chronic pain in the lumbar region. For this, a randomized, placebo-controlled, triple blind trial will be conducted, for which 72 volunteers will be recruited, randomly assigned to two experimental groups. The volunteers will receive phototherapy with the device that covers an area of 252 cm2 in the lumbar region. The treatment was carried out twice a week, for three weeks, with a total of 6 sessions. After treatment with phototherapy, volunteers will be evaluated according to the degree of pain classification (VAS) and range of motion (ROM) of the lumbar region. It was observed, a statistically significant (p<0.05) decrease in relation to the intensity of pain, of the active group when compared to the placebo group. It is concluded that PBMT showed improvement in chronic low back pain.